TikTok Platform to Train Middle School Students' Computational Thinking Skills in Distance Learning - Reskianissa, Anastasya; Sakti, Asri Wibawa; Azizah, Nissa Nur (Bumi Publikasi Nusantara, 2022)
The competence of students in Indonesia is still in a low rank based on their problem-solving and reasoning abilities. The pandemic condition forces distance learning to hinder the improvement of students' abilities if there is no innovation in learning that can help students to always be motivated in learning. This study aims to determine the effectiveness of using TikTok as a learning media innovation to train computational thinking skills, especially in the distance learning process. The research method uses a quantitative approach with the target of 9th-grade junior high school students. The results of the study showed that the post-test average of students was 89.3%, increasing 32.2% from the pre-test results which only reached 57.1%. This shows that short videos uploaded through TikTok can be an effective and innovative learning media.